Optical, morphological and photocatalytic properties of biobased tractable films of chitosan/donor-acceptor polymer blends. (1st December 2020) - Jessop, I.; Albornoz, J.; Ramírez, O.; Durán, B.; Molero, L.; Bonardd, S.; Kortaberria, G.; Diaz Diaz, D.; Leiva, A.; Saldías, C.
Highlights: Chitosan/donor-acceptor polymer films were obtained by solvent-casting-method. These "all-polymer" films can be considered as biobased tractable materials. The biobased films showed convenient photocatalytic activity. These economically viable raw materials are attractive for technological uses. Abstract: Biobased tractable films consisting of blends of chitosan (CS) with polymer bearing carbazole derivatives as pendant groups and fluorene-thiophene as donor-acceptor units (referred to as DA) were prepared, and their optical, morphological and photocatalytic properties were studied. DA was dissolved in tetrahydrofuran (THF) and mixed with an acidified aqueous solution containing chitosan to obtain chitosan/DA (CS/DA) films by solution casting. The fabricated biobased films were characterized using spectroscopic techniques (FT-IR and UV–vis), thermogravimetry, mechanical assays, contact angle analysis, and atomic force microscopy (AFM). The effects of varying DA compositions and the results of exposure to visible-light irradiation of the films were also analyzed. The results indicated the existence of interactions between chitosan and DA and a potentially profitable light-driven response of these biobased films. This behavior was reflected in the optical, topographical, and contact angle properties of the films, which exhibited different characteristics before and after visible-light exposure. Finally, the photocatalytic performance of the biobased films was tested via the decomposition of methyl orange (MO), as a reaction model system. Our results revealed a significant photocatalytic activity (according to biobased film composition, approximately 64 % and 87 % of methyl orange were degraded under continuous visible-light irradiation for 120 min) of the films which is attributed to the combined presence and synergetic effects of the film-forming ability of chitosan and the photoproperties of DA.